Panic disorder in alcohol dependency: a retrospective study - Arıkan, Zehra; Çepik Kuruoğlu, Aslı; Aslan, Selçuk (Journal of Dependence, 2002)
Objective: There is a high rate of comorbidity between panic disorder and alcohol abuse. Some authors propose that the patients use alcohol as a self-medication to decrease the frequency and intensity of panic attacks. However, it is largely accepted that both disorders share a common biological background. In this study we retrospectively evaluated the patients with dual diagnosis of alcohol dependency and panic disorder.Method: The charts of the patients hospitalized during 1993-2001 in alcohol dependency treatment unit in Gazi University Faculty of Medicine were evaluated. The sociodemographic characteristics, disease features, and treatment response of 18 male patients with dual diagnosis of alcohol dependency and panic disorder were reviewed.Results: The mean age of the patients was 39.1 (2054). There was a high incidence of family history of psychiatric disorders including alcohol dependency. Ten (55.6%) of the patients reported alcohol abuse prior to panic disorder, while the remaining 8 (44.4%) of the patients experienced panic disorder first. Furthermore, an increase in alcohol abuse after the panic symptoms was observed in 6 (33.3%) of the patients while the rest (66.7%) denied any change in drinking habits.Conclusion: Panic disorder is commonly encountered in alcohol dependent patients. This condition can be explained by self-medication in some of the patients, while in most of the cases these two disorders are thought to originate from a common biological background.
Keywords: Alcohol dependency; panic disorder; comorbidity